The Application of Sky Quality Meter at Twilight for Islamic Prayer Time - Shariff, N.N.M.; Muhammad, A.; Zainuddin, M.Z.; Hamidi, Z.S. (IACSIT Press, 2012)
The aim of this study is to detect elusive lightthat indicate the prayer time (Isha’). Therefore, we focused on optical sky brightness at dusk from May 2007 through April 2008 intermittently. The measurements of twilight sky brightness were covered at one (1) site covering; West coast of Peninsular Malaysia. The measurements were done by applying Sky Quality Meter (SQM) which covered between400-700 nm in accordance of human eyes and SQM range. Results showed that there are clear indications of light changes when Sun at certain degree below horizon that visible by plateau form in twilight sky brightness dependences versus solar zenith angle. It is clarified that the yearly averages of solar depression by observation are best correlated within the range of 17.3o – 19.5o for Isha’.